Parent training for preschool ADHD: a randomized controlled trial of specialized and generic programs. (16th October 2014) - Abikoff, Howard B.; Thompson, Margaret; Laver‐Bradbury, Cathy; Long, Nicholas; Forehand, Rex L.; Miller Brotman, Laurie; Klein, Rachel G.; Reiss, Philip; Huo, Lan; Sonuga‐Barke, Edmund
<x xml:space="preserve">Abstract</x> Background The 'New Forest Parenting Package' (NFPP), an 8‐week home‐based intervention for parents of preschoolers with attention‐deficit/hyperactivity disorder (ADHD), fosters constructive parenting to target ADHD‐related dysfunctions in attention and impulse control. Although NFPP has improved parent and laboratory measures of ADHD in community samples of children with ADHD‐like problems, its efficacy in a clinical sample, and relative to an active treatment comparator, is unknown. The aims are to evaluate the short‐ and long‐term efficacy and generalization effects of NFPP compared to an established clinic‐based parenting intervention for treating noncompliant behavior ['Helping the Noncompliant Child' (HNC)] in young children with ADHD. Methods A randomized controlled trial with three parallel arms was the design for this study. A total of 164 3–4‐year‐olds, 73.8% male, meeting DSM‐IV ADHD diagnostic criteria were randomized to NFPP (N = 67), HNC (N = 63), or wait‐list control (WL, N = 34). All participants were assessed at post‐treatment. NFPP and HNC participants were assessed at follow‐up in the next school year. Primary outcomes were ADHD ratings by teachers blind to and uninvolved in treatment, and by parents. Secondary ADHD outcomes included clinician assessments, and laboratory measures of on‐task behavior and delay of gratification. Other outcomes included parent and teacher ratings of oppositional behavior, and parenting measures. (Trial name: Home‐Based Parent Training in ADHD Preschoolers; Registry: ClinicalTrials.gov Identifier: NCT01320098; URL: http://www/clinicaltrials.gov/ct2/show/NCT01320098). Results In both treatment groups, children's ADHD and ODD behaviors, as well as aspects of parenting, were rated improved by parents at the end of treatment compared to controls. Most of these gains in the children's behavior and in some parenting practices were sustained at follow‐up. However, these parent‐reported improvements were not corroborated by teacher ratings or objective observations. NFPP was not significantly better, and on a few outcomes significantly less effective, than HNC. Conclusions The results do not support the claim that NFPP addresses putative dysfunctions underlying ADHD, bringing about generalized change in ADHD, and its underpinning self‐regulatory processes. The findings support documented difficulties in achieving generalization across nontargeted settings, and the importance of using blinded measures to provide meaningful assessments of treatment effects.